Household Role in Coping with Precarious Work. Evidence from Qualitative Research in Urban Romania and Switzerland - Suter, Christian (My University, 2016)
This paper presents the results of a qualitative comparative study that looked at the meaning of ‘precarious work’ in households situated in the position of ‘precarious prosperity’ in Switzerland and Romania in 2013. The aim of this research is to explore the experiences of individuals with precarious work and to embed them into their household and national structural contexts. Employment patterns in the two countries are similar in terms of uncertainty and instability, yet vary in many other aspects. While in Romania insecurity is due mainly to the very low incomes, in Switzerland it stems from non- standard contracts. The research shows that for households of precarious prosperity, precarious work is both a strategy to cope with uncertainty and instability and a circumstance leading to precariousness. The analysis explores qualitatively the meaning that individuals living in households of precarious prosperity attribute to their employment situation as contextualized by the interplay between household and individual situation.
Keywords: Household; Precarious work; Romania; Switzerland